Niewydolność serca i płuc, transplantologiaCare of the potential lung donor – new challenge for the anesthetists in Poland - Nadziakiewicz, Paweł; Saucha, Wojciech; Wojarski, Jacek; Wilk, Jarosław; Zakliczyńska, Helena; Knapik, Piotr; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Transplantation in general and especially lung transplantations are limited by the shortage of suitable organ donors. Brain death is connected with many potentially harmful reactions. This can adversely affect organ function and initiate lung injury. Brain death is characterized by two hemodynamic phases. Massive sympathetic reaction initially results in hypertensive crisis which is followed by neurogenic hypotension. The systemic and lung inflammation occurs. Donor lung may become injured due to prolonged mechanical ventilation, inappropriate fluid resuscitation, neurogenic pulmonary edema, aspiration pneumonia or nosocomial pneumonia. Optimal care is necessary in the treatment of the potential organ donor to fulfill restrictive criteria for lung retrievement. The approach consists of appropriate ventilation, frequent suctioning of a bronchial tree, brochoscopy, fluid management and hormonal supplementation. In this review we present structured approach to the care of a potential donor. The optimatization of donor management and extension of selection criteria already increased the number of transplanted organs in the recent years. In Poland, continuous efforts should be done because of great disparity between the increasing number of potential recipients and available transplantable organs.